Non-Electric Shock Tube Initiation Systems Applications and Hookups - Tom Treleaven; John Watson (International Society of Explosives Engineers, 1995)
This guide presents nur-nerous patterns that provide 8 millisecond separations between initiated charges. The guide is tabulated in seven sections to provide Quick reference by number of decks or bunch blasting. The pattern IS presented in the section where the highe!$ number of decks works. It should be noted that patterns applicable to multipledackshwtings are alsoapplicsblefor fewer decks.